Indigenous Knowledge and Sustainable Development: The Case of Rwanda's Agricultural Sector. - Phaduli, Itani (Graduate School of Business (GSB), 2023)
The need for creating sustainable and relatable development projects has placed a sharp focus of the different approaches and methods of achieving development. Traditional development approaches such as top-down theory and the bottom-up theory of development have evolved over the years whilst recent approaches such as Randomised Controlled Experiments (RCE) have also emerged with the aim of creating sustainable and more relatable development projects. All these approaches of development have had their fair share of criticism and applauses in literature. The use of Indigenous Knowledge Systems (IK) as a factor of the bottom-up theory of development has been argued as an important element of advancing the developmental agenda and creating sustainable & relatable projects. Many scholars have conducted research around how IK can be incorporated in development projects around the world. Although research has been conducted, much is yet to be discovered around the actual impact or lack thereof of IK as a key factor of the bottom-up theory of development in development projects. This dissertation researched the impact of Rwanda's IK as a factor of the bottom-up theory of development with a focus on Rwanda's Land, Husbandry water harvesting and Hillside irrigation (LWH) project as a unit of analysis. Furthermore, the research assessed whether the Rwandan water harvesting, and irrigation IK played a role in the overall project conceptualization, design and implementation and if so, how this was incorporated in the overall project and finally what role (if any) this IK played in the overall outcomes of the LWH project. A qualitative case study research of the Rwanda's Land Husbandry, Water Harvesting and Irrigation Project was conducted within-depth questionnaires used as data collection instruments from farmers and project coordinators who were immensely involved in the design, development, implementation and monitoring of the project. Data analysis showed that most study participants agreed that the Rwandan water harvesting, and irrigation IK was incorporated in the LWH project and was a key success factor in the bottom-up theory used to implemented in the LWH project. The research found that the incorporation of IK as a factor of the bottom-up theory enabled quicker adoption of the project, increased levels of accountability and responsibility over the project by project beneficiaries and an accelerated attainment of project goals and objectives.